# What is the sum of the polynomials (7x^{3} - 4x^{2}) + (2x^{3} - 4x^{2})?

**Solution:**

Given: Polynomial is (7x^{3} - 4x^{2}) + (2x^{3} - 4x^{2})

Polynomials can be simplified by adding like terms.

On adding we get

(7x^{3} + 2x^{3} ) + ( - 4x^{2} - 4x^{2} )

= 7x^{3} + 2x^{3} - 4x^{2} - 4x^{2}

= 9 x^{3} + (- 8x^{2})

= 9 x^{3} - 8x^{2}

## What is the sum of the polynomials (7x^{3} - 4x^{2}) + (2x^{3} - 4x^{2})?

**Summary: **

The sum of the polynomials (7x^{3} - 4x^{2}) + (2x^{3} - 4x^{2}) is = 9 x^{3} - 8x^{2}